Implementation of Democratic Values in Islam to Build Student Character in the Millennial Era - Oktavia, Nela; Nurkhalizah, Siti (Jurnal Pendidikan Amartha, 2022)
The importance of implementing democratic values in the life of the nation and state for every citizen, especially for students as the younger generation of future leaders of the nation. In this current era, the character of the nation has experienced a decline due to various factors, both from itself and environmental factors so as to form an uneducated generation, such as promiscuity, discrimination between seniors and juniors, brawls that create unrest in society and even fall into drug use. Whereas in the past students were recorded as the genuine force of the reform movement in Indonesia. Sincerity, passion, and partiality to the fate of the people and the future of Indonesia have made students as agents of change that are always taken into account from time to time. So that democratic values are needed by the students of today's millennial generation for character building, because in essence the students are the generation of the nation's movers who are the successors of the future leadership. Democracy as a state political system that is seen as the best model and capital to manage political life, so that students' understanding of democratic values is an important investment in building character as a process towards achieving a civil society order based on Pancasila, students should prioritize exemplary attitudes and abandon behaviors that discriminate against others, by improving their abilities in accordance with their fields.